Experimental data at high PT and its interpretation: the role of theory - Belonoshki, A. B.; Rosengren, A. (Física de la Tierra, 2012)
Experiments, relevant for planetary science, are performed often under extreme conditions of pressure and temperature. This makes them technically difficult. The results are often difficult to interpret correctly, especially in the cases when experimental data are scarce and experimental trends difficult to establish. Theory, while normally is inferior in precision of delivered data, is superior in providing a big picture and details behind materials behavior. We consider the experiments performed for deuterium, Mo, and Fe. We demonstrate that when experimental data is verified by theory, significant insight can be gained.
Keywords: Earth’s Inner Core; Molecular Dynamics; Iron; Mo; Deuterium.